Jonas Wood - Brodbeck, Anna Katherine; Allan, Ken D. (Dallas Museum of Art, 2019)
Southern California-based painter Jonas Wood (b. 1977) depicts everyday scenes in a colorful, graphic style that references modernist and Pop aesthetics while remaining unquestionably contemporary. The first book to consider Wood's work in a scholarly, art-historical context, this mid-career survey cements his place in the lineage of artists who similarly embraced quotidian imagery and pictorial flatness to tell deeper stories, such as David Hockney, Henri Matisse, and Philip Guston. While based on intense real-life observation, Wood's paintings depict worlds that are ultimately fictive, subjected to a process of manipulation through preparatory photo collages. The authors hone in on Wood's ability to compose scenes dense with objects, people, and places that have intense personal meaning yet function allegorically to suggest universal situations and themes. Striking illustrations of Wood's pieces demonstrate how the personal has become public in the digital age, capturing the brilliance and depth of this artist on the rise